PENGARUH FLEXIBLE WORK ARRANGEMENT DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS PEKERJA LEPAS DI PROVINSI BALI - Damayanti, Ni Putu Sri; Suwandana, I Gusti Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
Flexible work arrangements have been widely used to meet the needs of workers and manage work. Flexible working hours and methods will make it easier for workers to coordinate their work and social schedules. The purpose of this study was to determine the effect of flexible work arrangements and job satisfaction on the productivity of freelancers. The population is all self-employed workers in Bali Province. The sample used in this study was 100 respondents who were collected during the 7 days of the survey. Data collection was obtained from the results of questionnaires which were distributed directly to all entrepreneurs in the province of Bali. Furthermore, to analyze the data used multiple regression analysis. The results of this study indicate that flexible work arrangements effectively affect the productivity of entrepreneurs. The reaction of the freelancers is that they believe that through this work system, they can manage their work schedule more flexibly and become happier and happier. more efficient and closer to the family. Job satisfaction has an impact on work efficiency. It can be seen that there is a significant positive correlation (correlation) between job satisfaction and productivity of freelancers.